A study on non-linear behavior of memristor emulator using multisim - Eadala Sarath Yadav; Rajesh B; Srinivasan C.R; Sai Kalyan P (Institute of Advanced Engineering and Science, 2019)
A Memristor (memory resistor) is a two terminal non-linear passive element used to relate magnetic flux with respect to electric charge. A Memristor opposes the flow of electric current across a device like a resistor but also remember the last charge that was flowing through it. Memristor is a fourth passive circuit element after inductor ‘L’ resistor ‘R’, and capacitor ‘C. The voltage and current relationship in a memristor is a multivariable function therefore analyzing the circuit is a difficult task. This paper depicts the designing of a memristor model emulator using multisim and studied about its linear and non-linear characteristics.